2018
DOI: 10.1109/tgcn.2018.2832658
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Aware Routing in Carrier-Grade Ethernet Using SDN Approach

Abstract: Soft-Defined Networking (SDN) is a new approach that enables operators to easily manage all the network elements.In this paper, we address the problem of energy-aware routing in SDN-based carrier-grade Ethernet networks. Our approach is based on turning off network nodes and links to reduce energy consumption, while respecting the rule space capacity for each Openflow switch, and maintaining an allowable maximum link utilization. The problem of identifying the optimal set of network elements to be turned off i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…To see the effectiveness of the PS, we compare it to two other approaches named minimum link on (MLO) and MNO [6 ]. In MLO, routing of flows is performed such that the number of active links in the network is minimised.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…To see the effectiveness of the PS, we compare it to two other approaches named minimum link on (MLO) and MNO [6 ]. In MLO, routing of flows is performed such that the number of active links in the network is minimised.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Our approach belongs to the Traffic Aware Energy efficiency approaches presented in this paper. The first-fit heuristic approach was used in [31]. Nodes and links are sorted using three criteria: Most-Power (MP), Least-Flow (LF), and Random (R).…”
Section: Network Energy Aware Approaches and Methodsmentioning
confidence: 99%
“…This condition can be a significant limitation to energyefficient routing in practical networks. It is observed that only SDN nodes and the connected links can get into sleep Finally, Maaloul et al, [67] considered energy saving problem in the case of carrier-grade Ethernet network. In their work, the authors suggested a traffic-aware routing and load balancing scheme to shut down the minimum set of network elements and links, so as to achieve energy-saving and QoS guarantees free of network performance degrading.…”
Section: A Load Balancing Studiesmentioning
confidence: 99%